A Decade of Research on Supervision and Accountability in Guidance and Counseling: A Systematic Review and Comparative Analysis between Indonesia and Global Contexts - Nadiya Kurniati; Nurul Afrianti; Muhammad Solehuddin (Universitas PGRI Yogyakarta, 2026)
Supervision and accountability are critical to improving the quality of guidance and counseling services, yet gaps remain in understanding their development and implementation, particularly in comparative contexts between Indonesia and the international community. (1) Objective: This study explores the development of supervision and accountability in guidance and counseling through a comparison of Indonesian cases with those in other countries. (2) Method: A systematic literature review was conducted in Google Scholar, Taylor & Francis, Sage Publication, Wiley, and Frontiers databases for the period 2015-2025. Inclusion criteria were peer-reviewed articles in English/Indonesian that discussed supervision and/or accountability practices, while exclusion criteria excluded non-empirical and irrelevant articles. (3) Results: Of the 1008 identified articles, 10 were selected, 4 Indonesian, 6 international. Indonesian research emphasized contextual adaptive technology supervision models, while international research developed evidence-based frameworks such as Ethical-Relational Clinical Supervision. (4) Implications: Supervision is a multidimensional construct that integrates technical, relational, and welfare aspects with the challenges of cultural adaptation. (5) Recommendations: Future research needs to develop an integrated model, explore the role of digital technology, and design supervision effectiveness measurement instruments that are sensitive to the local Indonesian context. Keywords: accountability, guidance and counseling, supervision